CUSTOMER EXPERIENCE MELALUI STRATEGI OMNICHANNEL: STUDI PADA INDUSTRI RITEL DI SEMARANG - Hadi, Arman; Ristianawati, Yuyun; Rosyada Fitriati, Ika (JURNAL ILMIAH EDUNOMIKA, 2025)
The rapid advancement of digital technology has transformed the retail industry, prompting businesses to adopt omnichannel strategies that integrate various sales channels to provide seamless and consistent shopping experiences. However, the extent to which these strategies enhance customer experience and foster customer loyalty remains a critical issue. This study aims to analyze the impact of omnichannel strategies on customer experience and their subsequent effect on customer loyalty in the retail industry of Semarang. A quantitative approach was employed, utilizing survey data from 250 respondents who had shopped at omnichannel retail stores. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine relationships between variables. The findings reveal that omnichannel strategies significantly enhance customer experience, particularly through channel integration, service consistency, and ease of access to information (β = 0.65; p < 0.01). However, these strategies do not directly impact customer loyalty (β = 0.12; p > 0.05); instead, customer experience acts as a mediating factor (indirect effect = 0.47; p < 0.01). The study's limitations include its focus on a single city, limiting generalizability to broader markets. Additionally, external factors such as pricing competition and cultural shopping preferences were not extensively examined. The findings suggest that merely implementing omnichannel strategies is insufficient to cultivate customer loyalty. Retailers must optimize personalized services and enhance the overall shopping experience to retain customers effectively. Future research should explore the role of big data and AI-driven personalization in strengthening omnichannel customer engagement across diverse retail landscapes.